MANAJEMEN RISIKO KESELAMATAN DAN KESEHATAN KERJA DALAM UPAYA PENCEGAHAN PENYAKIT AKIBAT KERJA - Munawaroh, Madinatul; Noprianty, Richa; Kurniawati, Ratna Dian; Winengsih, Ecih; Sutriyawan, Agung; Fauzi, Agung Ahmad; Rahayu, Sindi Sri; Raidinata, MB Ismu (Batara Wisnu : Indonesian Journal of Community Services, 2024)
Community members working process lemongrass fragrant will be exposed to exposure to chemical substances that have to use the device to protection as part of efforts to prevent diseases caused by their work. One of the problems of health in respiratory system that is due to a chemical substance pneumokoniosis, although the emergence of this disease needs long time, but it is still need to be given clear understanding and application on workers and also a society that participate in the health responsibilities of its environment